Can percussive intrapulmonary ventilation improve the efficacy of physiotherapy in children with cystic fibrosis? - Diletta Innocenti; Chiara Castellani; Eleonora Masi; Valeria Galici; Letizia Macconi; Giovanni Taccetti (Monaldi Archives for Chest Disease, 2023)
Lung disease in cystic fibrosis (CF) is characterized by reduced mucociliary clearance, airway plugging, recurrent infections and chronic pulmonary inflammation. Patients who are affected undergo daily respiratory physiotherapy to improve airway clearance. Intrapulmonary percussive ventilation (IPV) is a technique used in clinical practice, but it is not commonly used in CF patients. Evidence in various respiratory pathologies, particularly in children, is still lacking. We present the case of an eleven-year-old boy with cystic fibrosis who did not respond to traditional respiratory physiotherapy techniques. We proposed and tested the use of IPV during hospitalization. In this case, the use of IPV in physiotherapy treatment reduced the need for intravenous antibiotics, hospitalization, and improved radiologic features. IPV can be used successfully in CF patients who are resistant to traditional physiotherapy techniques.